If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 + 5x + -7x + -4 = 0 Reorder the terms: -2 + -4 + 3x + 5x + -7x = 0 Combine like terms: -2 + -4 = -6 -6 + 3x + 5x + -7x = 0 Combine like terms: 3x + 5x = 8x -6 + 8x + -7x = 0 Combine like terms: 8x + -7x = 1x -6 + 1x = 0 Solving -6 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 1x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 1x = 0 + 6 1x = 0 + 6 Combine like terms: 0 + 6 = 6 1x = 6 Divide each side by '1'. x = 6 Simplifying x = 6
| 23y-22y=-8-4 | | k/10=17/10 | | 2x+9=-4x-1 | | w/(w-5)-(3w)/(3w-5)=(w-2)/(3w^2-20w+25) | | 15x^3/10x | | 2x+y=-9*y | | 7(f+7)+6f=-8f-7(-7+3f) | | (16x/15)=16 | | -2=v-15 | | -5x=16 | | e/4-3=-6 | | 2/4-3=-6 | | 2x+y=-9fory | | 1/x+4/3x-5/6x+1 | | a-2=a/b | | xy=-3 | | 2y=42 | | -3[y-1]=9 | | 2x^2+9=81 | | 4x^2-324=0 | | (3-2g)7=5g-(2g+7) | | 18=9t-18 | | 1+3x=2x-9 | | b=1/3(h-1) | | 42-9x=44 | | 2(4-11)+9=19 | | 4(a-2)+2a=17 | | 3/8=21/n | | y^4-15y^3-14y^2+90y-350=0 | | 3[x+1]=7 | | 1.6=7.6-5(k+111) | | 4y-28=6y+3 |